Transcription of TIR1-Controlled Genes Can be Regulated within 10 Min by an Auxin-Induced Process. Can TIR1 be the Receptor? - Labusch, Corinna; Effendi, Yunus; Fulda, Martin; Scherer, Günther F. E. (Frontiers in Plant Science, 2016)
Abstract ABP1 and TIR1/AFBs are known as auxin receptors. ABP1 is linked to auxin responses several of which are faster than ten minutes. TIR1 regulates auxin-induced transcription of early auxin genes also within minutes. We use transcription of such TIR1-dependent genes as indicator of TIR1 activity to show the rapid regulation of TIR1 by exogenous auxin. To this end we used quantification of transcription of a set of fifteen early auxin-induced reporter genes at t=10 and t=30 min to measure this as a TIR1-dependent auxin response. We conducted this study in 22 mutants of auxin transporters (pin5, abcb1, abcb19, aux1/lax3), protein kinases and phosphatases (ibr5, npr1, cpk3, CPK3-OX, d6pk1, d6pkl1-1, d6pkl3-2, d6pkl1-1/d6pkl2-2, d6pkl1-1/d6pkl3-2), of fatty acid metabolism (fad2-1, fad6-1, ssi2, lacs4, lacs9, lacs4/lacs9) and receptors (tir1, tir1/afb2, tir1/afb3) and compared them to the wild type (wt). After 10 min auxin application, in 18 out of 22 mutants mis-regulated expression of at least one reporter was found, and in 15 mutants transcription of two-to-threee out of five selected auxin reporter genes was mis-regulated. After 30 min of auxin application to mutant plants, mis-regulation of reporter genes ranged from one to 13 out of 15 tested reporter genes. Those genes chosen as mutants were themselves not regulated in their expression by auxin for at least one hour, excluding an influence of TIR1/AFBs on their transcription. The expression of TIR1/AFB genes was also not modulated by auxin for up to 3 h. Together, this excludes a feedback or feedforward of these mutant genes/proteins on TIR1/AFBs output of transcription in this auxin-induced response. However, an auxin-induced response needed an as yet unknown auxin receptor. We suggest that the auxin receptor necessary for the fast auxin-induced transcription modulation could be, instead, ABP1. The alternative hypothesis would be that auxin-induced expression of a protein, initiated by TIR1/AFBs receptors, could initiate these responses and that this unknown protein regulated TIR1/AFB activities within 10 min.